2006
DOI: 10.1038/sj.npp.1301013
|View full text |Cite
|
Sign up to set email alerts
|

DHEA, a Neurosteroid, Decreases Cocaine Self-Administration and Reinstatement of Cocaine-Seeking Behavior in Rats

Abstract: Dehydroepiandrosterone (DHEA), which can act as a potential antidepressant in both animals and humans, appears to lower distress involved with cocaine withdrawal. In fact, a role for neurosteroids in modulation of substance-seeking behavior is becoming increasingly clear. Therefore, we tested the effects of DHEA on the self-administration of cocaine (1 mg/kg/infusion) by rats. At maintenance, a relatively low dose of exogenous DHEA (2 mg/kg; i.p.) attenuated cocaine self-administration after several days of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The biopsychosocial model of challenge and threat may apply to the androgen DHEA in that the gain and loss framing instructions differentially impacted DHEA. We based the speculation that DHEA acted in line with reward cues largely on the literature on DHEA modulation of substance use seeking behaviors (Doron et al, 2006; Maayan et al, 2006), which tied this neurosteroid with reward-and motivation-related processes. Thus, while both DHEA and testosterone appeared stress-reactive, androgenic hormone rises may be driven by the motivation to complete a task and to successfully receive a performance-based incentive with the amount of intrinsic resources available to meet the expected demands.…”
Section: Discussionmentioning
confidence: 99%
“…The biopsychosocial model of challenge and threat may apply to the androgen DHEA in that the gain and loss framing instructions differentially impacted DHEA. We based the speculation that DHEA acted in line with reward cues largely on the literature on DHEA modulation of substance use seeking behaviors (Doron et al, 2006; Maayan et al, 2006), which tied this neurosteroid with reward-and motivation-related processes. Thus, while both DHEA and testosterone appeared stress-reactive, androgenic hormone rises may be driven by the motivation to complete a task and to successfully receive a performance-based incentive with the amount of intrinsic resources available to meet the expected demands.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have shown that selective removal of the adrenal medulla fails to alter norepinephrine levels within the central nervous system (CNS) (Peskind et al, 1986). DHEA administration has been reported to reduce cocaine SA and reinstatement (Doron et al, 2006), but the adrenal glands do not appear to be the source of DHEA in the brain (Corpechot et al, 1981). Although it is unlikely that a loss of aldosterone would directly contribute to our observed effects, we cannot rule out an indirect contribution of mineralocorticoid actions as a consequence of altered electrolyte balance, despite our attempts to stabilize sodium concentrations in our ADX rats through inclusion of NaCl in their drinking water.…”
Section: Extinctionmentioning
confidence: 99%
“…Brain punches were extracted in absolute ethanol. Aliquots (200 ml) of the resulting ethanol solutions were completely evaporated and subjected to a commercially available DHEA radioimmunoassay (RIA) kit (Diagnostic Systems Laboratories, Webster, TX (Doron et al, 2006;Maayan et al, 2000). This RIA utilizes DHEA-DSL 9000 Activet coated tubes.…”
Section: Extraction Of Brain Tissue and Dhea Radioimmunoassaymentioning
confidence: 99%